Analysis of factors that cause infants aged 0-6 months to not receive exclusive breastfeeding from their mother - Irdawati, Irdawati; Kusumawati, Yuli; Lestari, Widia; Fadhila, Vinda Nuri; Nafisah, Hasna (International Journal of Public Health Science (IJPHS), 2024)
Failure to give exclusive breastfeeding is a risk factor for stunting and malnutrition in toddlers. Other factors that may be the cause of a woman not giving exclusive breastfeeding must be known like family factors, health service factors or there are still other factors. The aim of this study to description the factors causing infants 0-6 months not to receive exclusive breastfeeding in the working area of the Gatak Health Center. The descriptive analytical research method with total sampling technique obtained a sample of 58 mothers who did not provide exclusive breastfeeding to their infants. The study found that the majority of mothers who did not provide exclusive breastfeeding were aged between 20 and 35 years old, had completed high school or vocational school education, and were employed. The 94.8% of the mothers had good health condition. External factors included mothers with good knowledge, lack of family support, and good support from healthcare workers. Factors causing mothers not to provide exclusive breastfeeding included their productive age and high level of knowledge, which made them prefer to work, resulting in less intensive time with their babies. Mothers felt that they lacked support from their families, which discouraged them from providing exclusive breastfeeding.